UNIVERSITY-SCHOOL PARTNERSHIP IN ACHIEVING THE VISION OF INDONESIA 2045 THROUGH RESEARCH TRAINING ON HIGH SCHOOL STUDENTS - Nurina Hasanatuludhhiyah; Annette d’ Arqom; Abdul Khairul Rizki Purba; Visuddho Visuddho; Deandra Maharani Widiatmaja; Ilham Rahmanto; Putu Bagus Dharma Permana (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
Universities participate in realizing Indonesia's vision 2045 “The Indonesians who are excellent, civilized, and mastering science technology, to bring Indonesia as the center of science technology development in the Asia and the world”. It would need intense effort and synergy, considering the science literacy of Indonesian students was ranked the 10th lowest out of 79 countries in 2018. The innovation capacity is ranked 74 out of 141 countries.  Research is an essential activity, encouraging the development of science technology. Research competency should be honed by high school students as part of scientific inquiry. Therefore, this community service was carried out in collaboration with FORISMA FK UNAIR, aimed to increase students’ understanding of the urgency, stages, and procedures of research as well as increase interest in research activities. It was also intended to develop their skills to compile and present research proposals. The partner was Raudlatul Jannah High School Sidoarjo. It was implemented through workshops, coaching, and presentations followed by the teachers and 11th-grade students.  The whole activity successfully improved students' knowledge. Increased knowledge score was obtained in 83% of participants. The pre-test evaluation showed 88% of participants had poor knowledge, whilst post-test evaluations were predominantly good. This community service increased students’ interest in research and changed their perceptions of research’s importance. This improved students' capability to identify research problems, search and compile scientific references as a basis for building hypotheses and conceptual frameworks, and determine research methods. The four groups of students were able to produce research proposals of sufficient quality and were able to present and discuss them in the forum. This community service was perceived to help the school in the implementation of curriculum, especially in science literacy. The school was committed to deepening students' knowledge and skills in the field of scientific research by providing research project modules. This community service is part of the contribution of higher education to the achievement of the vision of Indonesia 2045. This can be a model of scientific inquiry learning in secondary education, thus it is necessary to be implemented in other high schools.